Atmosphere/mantle coupling and feedbacks on Venus. Issue 6 (9th June 2014) - Gillmann, Cedric; Tackley, Paul
Abstract: We investigate the coupled evolution of the atmosphere and mantle on Venus. Here we focus on mechanisms that deplete or replenish the atmosphere: atmospheric escape to space and volcanic degassing of the mantle. These processes are linked to obtain a coupled model of mantle convection and atmospheric evolution, including feedback of the atmosphere on the mantle via the surface temperature. During early atmospheric evolution, hydrodynamic escape is dominant, while for later evolution we focus on nonthermal escape, as observed by the Analyzer of Space Plasma and Energetic Atoms instrument on the Venus Express Mission. The atmosphere is replenished by volcanic degassing from the mantle, using mantle convection simulations based on those of Armann and Tackley [2012], and include episodic lithospheric overturn. The evolving surface temperature is calculated from the amount of CO2 and water in the atmosphere using a gray radiative‐convective atmosphere model. This surface temperature in turn acts as a boundary condition for the mantle convection model. We obtain a Venus‐like behavior (episodic lid) for the solid planet and an atmospheric evolution leading to the present conditions. CO2 pressure is unlikely to vary much over the history of the planet, with only a 0.25–20% postmagma‐ocean buildup. In contrast, atmospheric water vapor pressure is strongly sensitive to volcanic activity, leading to variations in surface temperatures of up to 200 K, which have an effect on volcanic activity and mantle convection. Low surface temperatures trigger a mobile lid regime that stops once surface temperatures rise again, making way to stagnant lid convection that insulates the mantle. Key Points: A mantle‐atmosphere coupled model of Venus is investigated using volatile fluxes Realistic Venus‐like behavior is obtained for the mantle and atmosphere Feedback from surface conditions can have strong effects on mantle dynamics